The mechanism of multiple organ dysfunction syndrome in patients with COVID‐19. Issue 5 (8th February 2022) - Zhao, Wenbin; Li, Hanmeng; Li, Jianghua; Xu, Bin; Xu, Jian
Abstract: In late 2019, an outbreak of coronavirus disease 2019 (COVID‐19) arose, caused by severe acute respiratory syndrome coronavirus type 2 (SARS‐CoV‐2). This disease rapidly became a public health event of international concern. In addition to the most typical symptoms of dyspnea, numerous patients with COVID‐19 exhibited systemic symptoms, such as cardiovascular disease, liver and kidney failure, and disorders in coagulation. At present, clinical data indicates that numerous patients who are critically ill die from multiple organ dysfunction syndromes (MODS). Moreover, the entry of SARS‐CoV‐2 into cells causing severe pathology and progressive organ failure is precisely mediated by the human angiotensin‐converting enzyme 2 protein. This plays a role in maintaining both fluid and electrolyte homeostasis, ensuring the stability of the internal environment. Therefore, the present review aimed to investigate the pathogenesis of MODS caused by SARS‐CoV‐2 infection based on the current clinical data and previous studies. Highlights: Inflammatory factor storm, oxidative stress, and disseminated intravascular coagulation cause multiple organ dysfunction syndromes (MODS) in coronavirus disease 2019 patients. Angiotensin‐converting enzyme 2 (ACE2) protein, closely related to viral infection, mediates organ damage and causes MODS. Aging, underlying disease, and obesity downregulate ACE2 and may exacerbate MODS.